Optimized Expression Condition of CIDRα-PfEMP1 Recombinant Protein Production in Escherichia coli BL21(DE3): A Step to Develop Malaria Vaccine Candidate - Setyoadji, Winnie Almira; Sulistyaningsih, Erma; Kusuma, Irawan Fajar (Research Journal of Life Science, 2021)
Malaria is still an essential epidemiological disease worldwide, including in Indonesia. Several approaches are performed to control the disease, as well as vaccine development. The Cysteine-rich interdomain region α of Plasmodium falciparum erythrocyte membrane protein 1 (CIDRα-PfEMP1) is a pivotal domain in the malaria pathogenesis make it a malaria vaccine candidate. The development of the malaria vaccine is performed using recombinant technology. Recombinant protein production is an important step. The study aimed to determine the optimized condition for CIDRα-PfEMP1 recombinant protein expression in Escherichia coli BL21(DE3) expression system. Serial IPTG concentrations from 0.05, 0.1, 0.3, and 0.5 mM and two different incubation periods of 4 h and 8 h were optimized. The recombinant protein expression was visualized in SDS-PAGE, measured using the Bradford protein assay, and calculated using software Image J. SDS-PAGE visualization showed a 27 kDa band expressed CIDRα-PfEMP1 recombinant protein. The optimized condition for CIDRα-PfEMP1 recombinant protein expression was at 0.03 mM IPTG concentration and 8 h incubation period.